2020
DOI: 10.1002/ese3.670
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of actuator disks for wind turbines

Abstract: The expenses of a wind turbine modeling in particular a wind farm modeling either numerically or experimentally cause to take the advantages of actuator disks (AD). Porous disks (PD) are used to simulate actuator disks in experiments especially for wake studies. A rotor of a wind turbine replaced by a PD can be modeled efficiently with less cost and process time. For a proper PD selection, some semi‐empirical equations are suggested for a range of solidity of 0.2‐0.6. These equations came from a number of test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Experimental and numerical investigations on bare wind turbines have shown that their maximum power coefficient is in the range of Betz-limit [45,46]. In order to investigate the effects of the duct on the performance of wind turbines, two simulations of a VAWT with and without the duct were done.…”
Section: Ducted Wind Turbine: Numerical Approachmentioning
confidence: 99%
“…Experimental and numerical investigations on bare wind turbines have shown that their maximum power coefficient is in the range of Betz-limit [45,46]. In order to investigate the effects of the duct on the performance of wind turbines, two simulations of a VAWT with and without the duct were done.…”
Section: Ducted Wind Turbine: Numerical Approachmentioning
confidence: 99%
“…It can capture the wind turbine's wake features while making the setup simple and convenient. The design of these PDs is adapted from the model of Ranjbar et al 21 All PDs have the same diameter of 0.196 m and a uniform thickness of 2.8 mm. They are made of Plexiglass and were manufactured using laser cut with an accuracy of ±0.1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The first layer thickness of the grid and the growth rate along walls 21 are selected to be 0.1 and 1.8 mm, respectively.…”
Section: Numerical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to results reported by Xiao et al, 41 which reported lower velocity deficit in the wake of a perforated disk with 75% blockage compared to the wake of a solid disk. Ranjbar et al 42 investigated the drag, induction factor, and the power coefficient estimated from the induction factor for porous disks of different solidities. Recently, Huang et al 43 introduced a new scaling parameter D Ã ¼ 4A=P, with A being the disk area and P the perimeter, to match the wake recovery of porous disks of different geometries: circular, square, and rectangular.…”
Section: Introductionmentioning
confidence: 99%